x+(4x-24)=x+(3x+19)

Simple and best practice solution for x+(4x-24)=x+(3x+19) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(4x-24)=x+(3x+19) equation:


Simplifying
x + (4x + -24) = x + (3x + 19)

Reorder the terms:
x + (-24 + 4x) = x + (3x + 19)

Remove parenthesis around (-24 + 4x)
x + -24 + 4x = x + (3x + 19)

Reorder the terms:
-24 + x + 4x = x + (3x + 19)

Combine like terms: x + 4x = 5x
-24 + 5x = x + (3x + 19)

Reorder the terms:
-24 + 5x = x + (19 + 3x)

Remove parenthesis around (19 + 3x)
-24 + 5x = x + 19 + 3x

Reorder the terms:
-24 + 5x = 19 + x + 3x

Combine like terms: x + 3x = 4x
-24 + 5x = 19 + 4x

Solving
-24 + 5x = 19 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-24 + 5x + -4x = 19 + 4x + -4x

Combine like terms: 5x + -4x = 1x
-24 + 1x = 19 + 4x + -4x

Combine like terms: 4x + -4x = 0
-24 + 1x = 19 + 0
-24 + 1x = 19

Add '24' to each side of the equation.
-24 + 24 + 1x = 19 + 24

Combine like terms: -24 + 24 = 0
0 + 1x = 19 + 24
1x = 19 + 24

Combine like terms: 19 + 24 = 43
1x = 43

Divide each side by '1'.
x = 43

Simplifying
x = 43

See similar equations:

| 3x^2-22=12 | | 6y^5+9y^3-4y^2-6=0 | | (x*3)-(48*72)=3456 | | Solvem-4n=8form | | 5/12=x/108 | | 3v+14=59 | | -4x^2-10=-2(5-x^2) | | (x*3)-(48*y)=3456 | | y=5/4*5/4+10 | | 9y^2+3y=0 | | x/8+15=32 | | x/8+15 | | .50n=-101 | | y/3=4x-3 | | 4x+3y=-y | | 43.75=7w | | 2v=25.6 | | 0.4+3(1.2t+0.9)=21.1 | | 8=z+9 | | -5-5a=5(1+a) | | y=-4/9*4+4 | | y=-4/9(-4/9)+4 | | 3x=5(3x-8) | | 5x+3y=80 | | 3x+7(2x-8)=15 | | -27=12w+27 | | 5n^2-15n=0 | | 2x+x+16=32 | | -21=n*3+2 | | 32=30-k/16 | | 5n*2-15n=0 | | 9x-3=15x+12 |

Equations solver categories